LATVIAN ADAPTATION OF MCARTHUR-BATES COMMUNICATIVE DEVELOPMENT INVENTORIES - Vulāne, Anna; Urek, Olga; Markus, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article discusses the methodology and the preliminary results of the research project entitled “Latvian language in Monolingual and Bilingual Acquisition: tools, theories and applications” (LAMBA). The project involves 25 researchers – linguists, educators, psychologists – from five institutions in Latvia and Norway, and focuses on phonological, lexical and morphosyntactic acquisition of Latvian as a native language in monolingual and bilingual settings. One of the main goals of the project is to develop a set of norm-referenced language assessment tools that would allow for accurate and time-efficient evaluation of language development in pre-school children.The article will focus specifically on the Latvian adaptation of MacArthur-Bates Communicative Development Inventories – a parental report tool that assesses the development of receptive and productive vocabulary, and certain aspects of grammar. Two CDI forms were adapted in the project: CDI Words and Gestures designed for use with children between 8 and 16 months of age, and CDI Words and Sentences designed for 16- to 36-month old children. Each CDI form contains extensive and language-specific checklists of lexical items, communicative gestures and grammatical constructions.